Tổng hợp và cấu trúc của một vài hợp chất chứa dị vòng 1,2,4-triazol dẫn xuất của safrol - Hoan, Phạm Văn; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
Some compounds containing 1,2,4-triazole heterocycles derivated from safrole had been synthesized. Their UV, IR, NMR and MS spectra had been analysed accurately. The analysises UV, IR, NMR and MS spectra show that the structure of the synthesized compounds were properly suitable for intending synthesises.